The Development of "EKA-DM" Enteral Nutrition Formula Based on Edamame and Cinnamon for Type 2 Diabetes Mellitus - Ifda Kurnia Hamidatuzzahroh; Yohanes Kristianto; Etik Sulistyowati (Journal of Global Nutrition, 2025)
The prevalence of Type 2 Diabetes Mellitus (T2DM) in Indonesia tends to increase. One approach to managing diabetes in hospitals is administering of specialized formulas. This study aims to develop an enteral formula based on edamame flour and cinnamon powder (EKA-DM) for T2DM. The composition of the enteral formula ingredients was determined using a trial-and-error design by adjusting the weights of the components to achieve nutritional content that meets dietary requirements. The resulting formula was then evaluated regarding viscosity, osmolarity, NGT tube flowability, hedonic quality, and CDR color tests. Data analysis was conducted using univariate and bivariate approaches. The developed enteral formula “EKA-DM” in 1000 ml, provides 1013.59 kcal, with an energy density of 1.01 kcal/ml, 43.51 grams of protein, 52.79 grams of fat, 103.24 grams of carbohydrates, and 35.94 grams of dietary fiber. The viscosity and osmolarity of the formula were 10.00 mPa’s and 380 mOsm/L. Hedonic testing showed a significant difference in the taste of the enteral formula (p=0.045). The best formula, according to the panelists, was F3, with an edamame flour:cinnamon powder ratio of 65:35. Future studies are recommended to assess the formula’s glycemic index and shelf life.